Encouraging 5-year olds to attend to landmarks: a way to improve children's wayfinding strategies in a virtual environment - Lingwood, Jamie; Blades, Mark; Farran, Emily K.; Courbois, Yannick; Matthews, Danielle (Frontiers in Psychology, 2015)
Wayfinding is defined as the ability to learn and remember a route through an environment. Previous researchers have shown that young children have difficulties remembering routes. However, very few researchers have considered how to improve young children's wayfinding abilities. Therefore, we investigated ways to help children increase their wayfinding skills. In two studies, a total of 72 5-year olds were shown a route in a six turn maze in a virtual environment and were then asked to retrace this route by themselves. A unique landmark was positioned at each junction and each junction was made up of two paths: a correct path and an incorrect path. Two different strategies improved route learning performance. In Experiment 1, verbally labeling on-route junction landmarks during the first walk reduced the number of errors and the number of trials to reach a learning criterion when the children retraced the route. In Experiment 2, encouraging children to attend to on-route junction landmarks on the first walk reduced the number of errors when the route was retraced. This was the first study to show that very young children can be taught route learning skills. The implications of our results are discussed.